Analisis Kebijakan KPU dalam Rekrutmen KPPS untuk Pemilu 2024 - Bobby J Yuri; Aidinil Zetra; Roni Ekha Putera (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
Ad Hoc bodies as the main actors in the election stage should get great attention. The 2019 elections in Indonesia leave many problems that must be resolved to prepare for the 2024 elections. Problems such as the death of officers of the Voting Organizing Group (KPPS) and violations of election stages that often occur in ad hoc bodies. This must be minimized. In the 2020 Regional Elections there were other problems related to the fulfillment of the number of applicants for ad hoc bodies, in some regions an extension of recruitment time was needed to meet them. A policy of the General Election Commission (KPU) is needed as an election organizer. The KPU issued a policy as stated in KPU Regulation Number 8 of 2022 concerning the Establishment and Work Procedures of the Adhoc Agency for the Implementation of General Elections and Elections for Governors and Deputy Governors, Regents and Deputy Regents, and Mayors and Deputy Mayors. This research uses a descriptive method of analysis with data collection techniques using literature studies from various relevant sources. The results of the study illustrate that KPU makes policies to meet the needs of qualified ad hoc bodies. The recruitment process is carried out transparently using information technology, age restrictions are carried out to ensure the safety of the work of ad hoc bodies. As well as policies related to the increase in honorary money for ad hoc bodies.